Building Children's Character From Afar: Strengthening The Role of Indonesian Migrant Worker Mothers In Hong Kong - Hidayat, Muhamad Taufik; R, Rizka; Rahmawati, Nabila; Winaryati, Eny; Rahmawati, Fitri Puji (Yayasan Daarul Huda Kruengmane, 2023)
The objective of this community service program is to provide detailed guidance on how IMW mothers, many of whom have completed senior high school, can continue to support the character education of their 6-12-year-old children from a distance. The program aims to enhance the knowledge and skills of IMW mothers in recognizing, understanding, and supporting the character development of their children, even while they are abroad. The execution of the community service activity comprises three stages: (1) Preparation: This phase involves communication with partners, particularly The Special Branch of Aisyiyah (PCIA) Hong Kong, as well as liaising with other relevant parties such as the Indonesian Consulate General in Hong Kong (KJRI Hong Kong) and other IMW community members. (2) Education: Providing education to the community by delivering materials. (3) Counseling: Counseling sessions are conducted with some participants, addressing their stories and challenges, particularly in relation to their relationships with their children. Despite being physically distant from each other, Indonesian Migrant Worker mothers have significant potential to foster character development in their children. Through active communication, modeling positive behavior, instilling values, nurturing creativity, emotional management, as well as religious education and ethics, mothers can contribute to shaping their children's characters with strength and integrity. Consequently, they not only contribute to the economy but also represent a valuable moral legacy for future generations.